Integrated Energy Consumption Analysis of Autonomous Mobile Robots: A Sensor Fusion Framework with Real-Time SOC Awareness - Malik, Abdul (My University, 2025)
With the increasing deployment of autonomous mobile robots across industries like logistics, agriculture, defense and healthcare, optimizing energy consumption has become crucial for enhancing efficiency and extending operational lifetime. This research presents a comprehensive study on modeling energy consumption in mobile robots by integrating computational, mechanical, and communication components. Two custom mobile robots have been developed based on NVIDIA Jetson devices (Nano and TX2) as companion computers. Moreover, a real-time energy measurement system was developed using HSTS016L Hall-effect current sensors and ADS1115 analogue-to-digital Converter (ADC) to analyze power consumption across different robot subsystems. The study highlights the interdependence between mechanical actuation, computational workload, and battery state-of-charge (SOC), demonstrating how these factors collectively influence overall energy efficiency. Experimental results show that the battery's SOC has a significant impact on energy consumption. In the rover setup using the Jetson TX2, energy usage varied by up to 13.5 J for mechanical units and 10 J for computational units as the SOC ranged from 10% to 100%. These findings highlight the importance of a runtime SOC-aware control mechanism to optimize energy efficiency in mobile robots, enabling them to adapt their strategies based on real-time battery status. Furthermore, the study quantifies communication energy in multi-robot systems, achieving 10-15% efficiency gains through adaptive protocols. By addressing the critical gap in unified, SOC-aware energy models, this research provides a robust predictive framework, validated through controlled experiments, that enhances operational longevity and informs energy-efficient designs. These findings lay a foundation for sustainable robotic systems, enabling scalable, energy-aware deployments in real-world applications such as swarm robotics and remote exploration.
Keywords: Energy Consumption Modeling, Autonomous Mobile Robots, State of Charge (SOC) Awareness, Sensor Fusion, NVIDIA Jetson, Communication Energy Optimization, Multi Root System